DEGRO guideline for personalized radiotherapy of brain metastases and leptomeningeal carcinomatosis in patients with breast cancer - Borm, Kai Joachim; Behzadi, Sophie T.; Hörner-Rieber, Juliane; Krug, David; Baumann, Rene; Corradini, Stefanie; Duma, Marciana Nona; Dunst, Jürgen; Fastner, Gerd; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; et al. (Strahlentherapie und Onkologie, 2024)
The aim of this review was to evaluate the existing evidence for radiotherapy for brain metastases in breast cancer patients and provide recommendations for the use of radiotherapy for brain metastases and leptomeningeal carcinomatosis.
Gesehen am 03.07.2024